2016
DOI: 10.1080/02791072.2016.1229875
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Use, Acute Subjective Experiences, and Motivations for Using Synthetic Cathinones (“Bath Salts”) in Recreational Users

Abstract: Given the variety and potential toxicity of synthetic cathinones, clinicians and educators would benefit from information about patterns of and motivations for use, frequency of psychosocial consequences, and experience of acute subjective effects. We administered a comprehensive, web-based survey to 104 recreational users of synthetic cathinones. Sixty percent of respondents consumed synthetic cathinones once or more per month, usually snorting or swallowing these drugs, typically at home, usually with others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…In 2011, the United States Drug Enforcement Administration added synthetic cathinones to the Schedule I list of controlled substances (Drug Enforcement Administration, 2011). Despite their illicit status, these substances are still abused recreationally (Ashrafioun et al, 2016) and new derivatives continue to be introduced to the illicit drug market.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, the United States Drug Enforcement Administration added synthetic cathinones to the Schedule I list of controlled substances (Drug Enforcement Administration, 2011). Despite their illicit status, these substances are still abused recreationally (Ashrafioun et al, 2016) and new derivatives continue to be introduced to the illicit drug market.…”
Section: Introductionmentioning
confidence: 99%
“…However, these patterns are an aggregation and cumulation of multiple and complex decisions by individual members of communities and societies. Reports from medical settings and poison information centres do not provide information about reasons for consumers starting use of these molecules (Ashrafioun et al, 2016).…”
Section: 4: Investigating Motivations For Using Psychoactive Substamentioning
confidence: 99%
“…The number of papers which have come closest to achieving this is very small, i.e. : Winstock et al (2011a); Cahart-Harris et al 2013; Johnson and Johnson (2014); and Ashrafioun et al (2016). The first paper demonstrated that a web-based survey recruiting from an existing survey (Mixmag) could be employed to study users' experiences, but only contained a limited number of questions exploring motivations for use of particular types of synthetic cathinones.…”
Section: Attempting To Establish a Connection Between Different Typesmentioning
confidence: 99%
See 2 more Smart Citations